Twelve EU Countries on the Eastern Flank of NATO: What about Ukraine? - Przemysław Żurawski vel Grajewski (East/West: Journal of Ukrainian Studies, 2021)
The Trimarium Initiative (TI) is a platform for co-operation of twelve central and eastern European (CEE) countries of the eastern flank of the European Union (EU), introduced by Poland and Croatia in 2015. The TI is based on member co-operation in the development of transport and communication, energy, raw materials (gas and oil) transfer infrastructure, and digitization. The region is an important and rapidly growing market, and the TI goal is to boost economic co-operation among these twelve countries. Ukraine is not an EU member state, so it cannot be a full member of the TI; however, several TI infrastructural projects are open to Ukrainian companies. As Russia’s aggressive energy policy impacts Poland, Ukraine, the Baltic states, Scandinavia, and Slovakia, the TI has a potential to meet this challenge. Transport and communication and energy transit infrastructure are promising areas of co-operation among TI countries and Ukraine. U.S. support has added optimism and prestige to the initiative.